Синтез, фізико-хімічні та біологічні властивості (3-R-2-оксо-2H-[1,2,4]триазино[2,3-c]хіназолін-6-іл)карбонових кислот та їх похідних - Скорина, Дмитро Юрійович; Skoryna, D. Ju. (Запорізький державний медичний університет, 2015)
В дисертаційній роботі вперше досліджені умови, закономірності перебігу та препаративні обмеження реакцій [5+1]-гетероциклізації 6-R-3-(2-амінофеніл)-1,2,4-триазин-5-oнів із хлорангідридами, ангідридами аліфатичних дикарбонових кислот, несиметричними ангідридами аліфатичних дикарбонових кислот, ангідридами фталевої, біцикло[2.2.1]гепт-5-ен-ендо,ендо-2,3-, 7-oксобіцикло[2.2.1]гепт-5-ен-ендо,ендо-2,3- та циклогекс-4-ен-1,2-дикарбонових кислот, розроблені методи синтезу нових гетероциклічних систем на їх основі та створено комбінаторну бібліотеку з аналгетичною, антигіпоксичною, актопротекторною, церебро- протекторною та протипухлинною дією для пошуку «сполук-лідерів». Структура синтезованих сполук підтверджена ІЧ-, УФ-, 1H, 13C ЯМР-, хромато-мас-, мас-спектрами та рентгеноструктурним аналізом. Виявлено натрій (3-метил-2-оксо-2H-[1,2,4]триазино[2,3-c]хіназолін-6-іл)-бутаноат – практично нетоксичну сполуку (ЛД50 1500±156 мг/кг), яка підвищує фізичну витривалість за умов нормо-, гіпер- та гіпотермії, динамічну та статичну витривалість на моделях циркуляторної та гемічної гіпоксії, запобігає летальності піддослідних тварин з гострим порушенням мозкового кровообігу і, як наслідок, проявляє високу актопротекторну, антигіпоксичну та церебропротекторну активність. Conditions, features and preparative limitations of [5+1]-heterocyclisation reactions of 6-R-3-(2-aminophenyl)-1,2,4-triazine-5-ones with acylhalides, anhydrides of symmetric and non-symmetric aliphatic dicarboxylic acids, anhydrides of phthalic, bicyclo[2.2.1]hept-5-en-endo,endo-2,3-, 7-oxobicyclo[2.2.1]hept-5-en-endo,endo-2,3- and cyclohex-4-en-1,2-dicarboxilic acids have been studied in presented work for the first time. Synthetic protocols for novel heterocyclic system and related combinatorial libraries of compounds with analgesic, antihypoxic, actoprotective, cerebroprotective and anticancer activities have been discussed to discover a «lead-compounds». It has been shown that interaction of 2-R-[2-[quinazolin-4(3H)-ylydenhydra-zono]acetic acids and 3-R-[1,2,4]triazino[2,3-c]quinazolin-2-ones with hydrazine hydrate is a convenient method for synthesis of corresponding 6-R-3-(2-aminophenyl)-1,2,4-triazine-5-ones. Convenient protocols for synthesis of (3-R-2-oxo-2Н-[1,2,4]triazino[2,3-с]-quinazoline-6-yl)alkylcarboxylic acids based on [5+1]-heterocyclisation reaction of 6-R-3-(2-aminophenyl)-1,2,4-triazin-5-ones with acylhalides and anhydrides of symmetric and non-symmetric aliphatic dicarboxylic acids have been proposed. It has been shown that interaction of 6-R-3-(2-aminophenyl)-1,2,4-triazine-5-ones with anhydrides of phtalic and bicyclo[2.2.1]hept-5-en-endo,endo-2,3-dicarboxilic acids anhydrides proceeded as «classic» acylation and yielded 2-[2-(6-R-5-oxo-2,5-dihydro-1,2,4-triazin-3-yl)phenyl]-1H- and [2-(6-R-5-oxo-2,5-dihydro-1,2,4-triazin-3-yl)phenyl]-1H-3a,4,7,7a-tetrahydro-4,7-methano-isoindol-1,3-diones. The regularities of [5+1]-heterocyclisation of 6-R-3-(2-aminophenyl)-1,2,4-triazin-5-ones with conformationally restricted anhydrides of 7-oxobicyclo[2.2.1]hept-5-en-endo,endo-2,3-dicarboxylic acids have been evaluated for the first time. It has been found that key-step in formation of 2(Е)-3-(3-methyl-2-oxo-2H-[1,2,4]triazino[2,3-c]-quinazolin-6-yl)acrylic acid were the series of tandem processes: acylation, of retro-Diels-Alder elimination of furan molecule, and cyclization process. It has been found that 6-R-3-(2-aminophenyl)-1,2,4-triazin-5-ones react with cyclohex-4-en-1,2-dicarboxylic acid anhydride resulting in novel heterocyclic system, namely 2-aryl-11,14b-dihydro-3H-isoindolo[2,1-a][1,2,4]triazino[2,3-c]quinazoline-3,10- (14H)-dione. The possible pathways of reaction have been discussed, and structures of other products have been evaluated via LC-MS method. Structural modifications of (3-R-2-oxo-2Н-[1,2,4]triazino[2,3-с]quinazolin-6-yl)-alkylcarboxylic acids, namely synthesis of sodium salts and amides have been conduc-ted. The mentioned transformations were aimed to improve the pharmaco-technological characteristics and purposeful search of the novel anticancer agents. Structure and physicochemical properties of synthesized compounds have been proved by complex of instrumental methods including IR-, 1H, 13C NMR-, chromato-mass-, mass-spectrometry and X-ray structural study. Particularities of 2-aryl-11,14b-dehydro-3H-isoindolo[2,1-a][1,2,4]triazino[2,3-c]quinazolin-3,10-(14H)-diones structure, namely presence in 1H NMR-spectrum of anomalously deshielded proton of position 14b at the 6.56-6.54 ppm and significant low-field shift (8.01-7.99 ppm) of proton in the 8th position caused by intramolecular hydrogen bond have been discussed. The obtained results of pharmacological studies allowed to conduct analysis of “structure – biological activities” correlations. It has been found that intensity of cerebroprotective activity has been stipulated as by 1,2,4-triazino[2,3-c]quinazoline fragment so by carboxyalkyl moiety in the 6th position as well as by alkyl or aryl group in the 3rd position. Analgetic and actoprotective activities were predominately peculiar for sodium (3-R-2-oxo-2H-[1,2,4]triazino[2,3-c]-quinazolin-6-yl)alkylcarboxilates and depended on the length of carboxyalkyl moiety in the 6th position and on the nature of substituent in the 3rd position. Also it has been found that introduction of carboxyalkyl moiety of different alkyl fragment length or conformational modification of molecule led to the loss of cytotoxicity. Thus, the mentioned approach of molecular optimization was irrational for constructing the novel antitumor agents. It has been found that sodium (3-methyl-2-oxo-2H-[1,2,4]triazino[2,3-c]quinazo-lin-6-yl)butanoate was almost non-toxic compound (LD50 1500±156 mg/kg), which increased physical endurance in normo-, hypo- and hyperthermic conditions, dynamic and static endurance during circulatory and hemic hypoxia, prevented lethality of experimental animals with acute dysfunction of cerebral blood flow and had high actoprotective, antihypoxic and cerebroprotective action.
Keywords: синтез; 6-R-3-(2-амінофеніл)-1,2,4-триазин-5-oни; хлорангідриди та ангідриди дикарбонових кислот; похідні (3-R-2-oксо-2Н-[1,2,4]-; триазино[2,3-с]хіназолін-6-іл)алкілкарбонових кислот; спектральні характеристики; біологічна активність; синтез; 6-R-3-(2-аминофенил)-1,2,4-триазин-5-oны; хлорангидриды и ангидриды дикарбоновых кислот; производные (3-R-2-oксо-2Н-[1,2,4]триазино[2,3-с]хиназолин-6-ил)алкилкарбоновых кислот; спектральные характеристики; биологическая активность; synthesis; 6-R-3-(2-aminophenyl)-1,2,4-triazin-5-ones; acylhalides; dicarboxylc acids anhydrides; derivatives of (3-R-2-oxo-2Н-[1,2,4]triazino[2,3-с]-quinazolin-6-yl)аlkylcarboxylic acids; spectral data; biological activity